PENGARUH BAHASA POSITIF DALAM MENINGKATKAN KESEJAHTERAAN PSIKOLOGIS - Agil Asyqar Purbaya Putra; Elvan Fanzi Hariangga; Geugeut Suryaning Kanyaah; Hudan Septian Nur Zaman (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2024)
Language plays a crucial role in shaping individuals' thoughts, emotions, and behaviors. This study explores the influence of positive language on enhancing psychological well-being, including life satisfaction, positive emotions, and healthy social relationships. Positive language, characterized by optimistic, appreciative, and respectful words, impacts how individuals perceive themselves and their surroundings. Using quantitative and qualitative approaches, this research analyzes the effects of positive language in daily interactions within family, educational, and workplace settings. The findings reveal that individuals who consistently use and receive positive language tend to exhibit higher levels of psychological well-being. Within families, positive language strengthens emotional bonds, reduces conflicts, and fosters a sense of togetherness. In educational settings, teachers utilizing positive language create supportive learning environments, boost student motivation, and enhance teacher-student relationships. In workplaces, communication based on positive language increases job satisfaction, improves team collaboration, and reduces employee stress. Additionally, this study identifies that positive language mediates the formation of emotions such as gratitude, happiness, and optimism, directly contributing to mental resilience. However, applying positive language requires awareness and strong communication skills. Barriers such as habitual use of negative language, lack of self-awareness, and exposure to toxic environments may reduce its effectiveness.